2020
DOI: 10.1590/1414-431x20198793
|View full text |Cite
|
Sign up to set email alerts
|

Aliskiren attenuates cardiac dysfunction by modulation of the mTOR and apoptosis pathways

Abstract: Aliskiren (ALS) is well known for its antihypertensive properties. However, the potential underlying the molecular mechanism and the anti-hypertrophic effect of ALS have not yet been fully elucidated. The aim of the present study was to investigate the role of ALS in mammalian target of rapamycin (mTOR) and apoptosis signaling using in vivo and in vitro models of cardiac hypertrophy. A rat model of cardiac hypertrophy was induced by isoproterenol treatment (5 mg Á kg-1 Á day-1) for 4 weeks, with or without ALS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…35 The mTOR can be directly activated by Akt, and also plays an important role in the metabolism, growth, and apoptosis of the nerve cells. 36 It was found that PA can inhibit the autophagy in hippocampus, repair synapses, and restore the autophagy flux by activating the mTOR signaling pathway, with an antidepressant effect on rats with chronic unpredictable mild stress. 37 The results of this study also showed that compared with those in the normal control group, p-Akt and p-mTOR protein levels in the Aβ 25-35 -induced injury group were significantly reduced ( P < .01), and compared with those in the Aβ 25-35 -induced injury group, p-Akt and p-mTOR protein levels in Aβ 25-35 -induced SH-SY5Y cells increased significantly in the different PA-treated groups ( P < .05 or P < .01, Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…35 The mTOR can be directly activated by Akt, and also plays an important role in the metabolism, growth, and apoptosis of the nerve cells. 36 It was found that PA can inhibit the autophagy in hippocampus, repair synapses, and restore the autophagy flux by activating the mTOR signaling pathway, with an antidepressant effect on rats with chronic unpredictable mild stress. 37 The results of this study also showed that compared with those in the normal control group, p-Akt and p-mTOR protein levels in the Aβ 25-35 -induced injury group were significantly reduced ( P < .01), and compared with those in the Aβ 25-35 -induced injury group, p-Akt and p-mTOR protein levels in Aβ 25-35 -induced SH-SY5Y cells increased significantly in the different PA-treated groups ( P < .05 or P < .01, Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…( Bahadir et al, 2018 ), and aliskiren (20 mg/kg/day; p.o.) ( Zhao et al, 2020 ), respectively. Groups from 3 to 7 received their respective treatments starting from day 13 after the first dose of CFA, and then continued for 3 weeks.…”
Section: Methodsmentioning
confidence: 98%
“…Several drugs targeting these functional protein kinases have been developed and tested. In the model of cardiac hypertrophy, mibefradil, rapamycin, and aliskiren are found to inhibit PI3K/Akt/mTOR-mediated autophagy to alleviate CM hypertrophy and reverse cardiac remodeling [31–33] . Similarly, metoprolol and bisoprolol inhibit PKC to reverse cardiac hypertrophy [34] …”
Section: Protein Kinases In Cardiovascular Diseasesmentioning
confidence: 99%
“…In the model of cardiac hypertrophy, mibefradil, rapamycin, and aliskiren are found to inhibit PI3K/Akt/mTOR-mediated autophagy to alleviate CM hypertrophy and reverse cardiac remodeling. [31][32][33] Similarly, metoprolol and bisoprolol inhibit PKC to reverse cardiac hypertrophy. [34] Atherosclerosis Atherosclerosis is progressive inflammatory progress and the primary cause of myocardial infarction (MI) and stroke.…”
Section: Mouse Reperfusion Injury↓ Cardiac Function↑mentioning
confidence: 99%